The Impact of Store Image, Customer Trust, and Perceived Service Quality on Repurchase Intention: Customer Satisfaction as a Mediator among Alfamart Consumers in Bandung - Rangga Roland Sehastian, Harly; Hafidh Nurmansyah, Abdul Ahmad (International Journal of Management Science and Information Technology, 2026)
The surge in the modern retail sector has amplified competition among minimarket franchises, forcing retailers to identify the key drivers of customer retention. This research investigates how Store Image, Customer Trust, and Perceived Service Quality Influence Repurchase Intention, positioning Customer Satisfaction as a mediator among Alfamart minimarket patrons in Bandung, Indonesia. Utilizing a quantitative explanatory approach, data were gathered through structured questionnaires from 110 purposively sampled respondents with prior shopping experience at Alfamart. Multiple linear regression and the Sobel test via SPSS version 26 were applied to evaluate direct and indirect hypotheses. The conceptual framework posits that Store Image, Customer Trust, and Perceived Service Quality positively impact Customer Satisfaction, which in turn fosters Repurchase Intention. Additionally, Customer Satisfaction is anticipated to bridge the gap between these three antecedents and the intent to repurchase. Theoretically, this study enriches retail marketing literature by offering fresh empirical insights into repurchase behavior within modern retail. Practically, the insights can guide Alfamart’s management and similar retail firms in crafting strategic initiatives to bolster satisfaction, loyalty, and sustainable repurchase rates.